Development of Digital Modules Based on Ethnomathematics of Sasak Tribe on Geometry Materials to improve Numeracy Skills of Elementary School Students - Hulaipah, Atikatul; Subarinah, Sri; Handika, Ilham (Universitas Muhammadiyah Mataram, 2025)
This study aims to determine the validity and practicality of the Sasak tribe's ethnomathematics-based digital module on geometry material and its effectiveness in improving elementary school students' numeracy skills. This research is highly urgent given the low numeracy skills of elementary school students and the need for learning innovations that are relevant to the local cultural context. Digital modules are a unique innovation for producing contextual and meaningful mathematics learning by integrating Sasak culture with geometry material through an interactive digital approach. This study employs the Research and Development (R&D) method using the ADDIE development model. Research instruments include expert validation questionnaires for media and materials, numeracy test questionnaires, teacher and student response questionnaires, and evaluation tests. The research subjects are fifth-grade students at SDN Gugus IV Perampuan, while the research object is the Sasak ethnic group-based ethnomathematics digital module on geometry material. The data were analyzed descriptively, quantitatively, and qualitatively, with normality, homogeneity, and t-tests to determine the differences in learning outcomes between the experimental and control classes, as well as N-Gain calculations to measure the improvement in elementary school students' numeracy skills. The results of the study show that the Sasak tribe's ethnomathematics-based digital module is highly valid, practical, and effective in improving elementary school students' numeracy skills. The Sasak ethnic mathematics-based digital module meets the requirements for content, presentation, and language validity. This module can help students understand geometric concepts in a contextual and meaningful way. It is very practical for teachers and students to use and effective in improving numeracy skills. Thus, the Sasak ethnic mathematics-based digital module has been proven effective in improving the numeracy skills of fifth-grade students at SDN Gugus IV Perampuan.